THE IMPACT OF ONLINE GAMES ON THE SOCIAL ATTITUDES OF CLASS III STUDENTS AT ELEMENTARY SCHOOL NEGERI 85 PRABUMULIH - Marina Meleniya; Murjainah; M.Taheri Akhbar (SMART: Journal of Multidisciplinary Educational, 2023)
Online games are games that use electronic media in the form of multimedia which are madeas attractive as possible so that players can get something so that there is inner satisfaction. Theaim of this research is to determine the impact of online games on students' social attitudes. Theresearch method that the author uses in this research is a qualitative descriptive approach. Datacollection techniques use observation, interviews and documentation. The results of the researchshow that students are able to implement social attitudes, even though there are still those who use online games at school, they still practice various aspects of social attitudes, such as aspects of discipline, students are able to come to school on time, and students are disciplined by obeying the rules. is at school. Schools are expected to provide infrastructure that can improve students' social attitudes and the school can also direct students to more positive activities.